2022
DOI: 10.1186/s40854-022-00341-w
|View full text |Cite
|
Sign up to set email alerts
|

Can news-based economic sentiment predict bubbles in precious metal markets?

Abstract: This study examines the role of market sentiment in predicting the price bubbles of four strategic metal commodities (gold, silver, palladium, and platinum) from January 1985 to August 2020. It is the first to investigate this topic using sentiment indices, including news-based economic and consumer-based sentiments developed using different methods. We observed the role of sentiment as a reliable indicator of future bubbles for some metal commodities and found that bubbles were regularly concomitant with bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 125 publications
(141 reference statements)
0
6
0
1
Order By: Relevance
“…constructed using machine-learning techniques. 7 The daily continuously compounded returns for each asset, r t , were computed as Li & Lucey, 2017;Maghyereh & Abdoh, 2022a, 2022bReboredo, 2013). Given the traditional motives of "flight-to-safety" from stocks to bonds, Baele et al (2020) showed that these motives correspond to heightened levels of volatility and a reduction in sentiment levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…constructed using machine-learning techniques. 7 The daily continuously compounded returns for each asset, r t , were computed as Li & Lucey, 2017;Maghyereh & Abdoh, 2022a, 2022bReboredo, 2013). Given the traditional motives of "flight-to-safety" from stocks to bonds, Baele et al (2020) showed that these motives correspond to heightened levels of volatility and a reduction in sentiment levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that gold generally performs a “safe haven” role (Baur & Lucey, 2010; Ciner et al, 2013; Li & Lucey, 2017; Maghyereh & Abdoh, 2022a, 2022b; Reboredo, 2013). Given the traditional motives of “flight‐to‐safety” from stocks to bonds, Baele et al (2020) showed that these motives correspond to heightened levels of volatility and a reduction in sentiment levels.…”
mentioning
confidence: 99%
“…Due to the high prices of Pt and Ir, many other potential catalysts that are more favorable, comparably active, and stable for both the ORR and the OER are still being searched. Ag is postulated as a possible alternative, since it is less expensive and shows a comparable ORR electrocatalytic activity to Pt in alkaline conditions. , Ag has been used in Siemens fuel cells in combination with nickel and titanium, and voltages around 800 and 900 mV at current densities of 400 and 200 mA cm –2 have been achieved, respectively . With gas diffusion electrodes (GDEs) made of Raney-silver and PTFE (polytetrafluoroethylene), voltages above 1 V and current densities around 30 mA cm –2 have been reached …”
Section: Introductionmentioning
confidence: 99%
“…Corbet and Connor (2021) found that pure silver must be mixed with other metal types because of its soft nature when forming another product. Another type of precious metal with a reasonably expensive price is Palladium (Maghyereh and Abdoh, 2022). It is a shiny white metal with the lowest melting strength This Journal is licensed under a Creative Commons Attribution 4.0 International License compared to others and is very dense, not easily damaged by chemical compounds and physical impact.…”
Section: Introductionmentioning
confidence: 99%